A preliminary study on the effects of radiation exposure on chondrocytes:: Sulphated Glycosaminoglycan (sGAG) content using cellular model - Mat Nawi, Nur Farhana; Zainuddin, Zainul Ibrahim; Sha'ban, Munirah (2016)
Radiation is known to be harmful to human health. However, the effect of radiation at cellular level has yet to be established. This study evaluated the possible effects of radiation on monolayer cultured chondrocytes. Rabbit’s chondrocytes were isolated, serially cultured and divided into two groups; (1) non-irradiated and (2) irradiated. Group 2 cells were subjected to irradiation after it reaches 80-90% confluency. Both groups 1 and 2 cells were taken out from the incubator, placed into a temperature-controlled container and were transported to a typical X-ray examination room. After irradiating group 2, both cell groups were returned into the incubator. Both groups were evaluated using morphological evaluation and sulphated glycosaminoglycan (sGAG) production at passages 0, 1, 2, and 3. All groups exhibited comparable morphological appearances throughout the passages. Both cell groups experienced gradual changes from chondrocytic to fibroblastic morphology. The non-irradiated group showed a decreasing trend of sGAG concentration after each successive passage. It is suggestive that when the optimum proliferating conditions of these cells were manipulated, stress was induced in the cells. Meanwhile, the irradiated group showed an increasing trend in relative sGAG concentration after each passage. This particular phenomenon is unexpected in view of the known harmful nature associated with radiation. This study suggested that the introduction of radiation exposure could have certain effects on the cartilaginous extracellular matrix (ECM) production. It is postulated that the induced radiation created a yet to be explained situation, where the cells tend to recover, regenerate and secrete extracellular matrix. Basically, this finding warrants further evaluation where gene expression and histological analysis will be conducted. The limitation of study includes the number of samples used (n=2). Future work involving more samples and subjecting the cells to irradiation up to passage 5 will be conducted.